A Step-by-Step Guide to Publishing Journal Article and Its Strategies - Hamzah, Muhammad Zilal; Abd Rahman, Nur Hayati; Sofilda, Eleonora; Nurhaida, Dida (Universitas Lancang Kuning, 2023)
Early researchers often struggle in writing scientific papers due to deficient writing skills and adapting to academic settings. In response, the Doctoral Program in Public Policy at the Faculty of Economics and Business at Universitas Trisakti organized a webinar with the intention of providing students with effective writing techniques. The webinar addressed important areas such as publishing in Scopus-indexed journals, composing successful manuscripts, maintaining writing consistency, and selecting appropriate venues for publication. The outcomes demonstrated that this webinar greatly enhanced the participants' confidence in scientific writing, with 85% strongly agreeing and 15% agreeing. Overall feedback from participants was positive, with 95% strongly agreeing and 5% agreeing that the activity was beneficial. Moreover, 90% expressed a strong wilingness to participate in future training, while 10% agreed. This paper's importance and benefits make it a valuable resource for widespread use, especially by new researchers aiming to enhance their scientific writing skills and strategies.